2022
DOI: 10.3390/cancers14030749
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1 Fusions and Basal Cells Contribute to Primary Resistance against Androgen Receptor Inhibition in TRAMP Mice

Abstract: Targeting testosterone signaling through androgen deprivation therapy (ADT) or antiandrogen treatment is the standard of care for advanced prostate cancer (PCa). Although the large majority of patients initially respond to ADT and/or androgen receptor (AR) blockade, most patients suffering from advanced PCa will experience disease progression. We sought to investigate drivers of primary resistance against antiandrogen treatment in the TRAMP mouse model, an SV-40 t-antigen driven model exhibiting aggressive var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In a recent study, the basal cell gene-expression profile was found to be significantly enriched in castration-resistant and advanced prostate cancers ( Zhang et al, 2016 ), which indicated basal cells might play a potential role in the development of resistance to anti-androgens in PCa. In a study published by Marhold et al showed that basal cells were involved in primary resistance to androgen receptor inhibition in the TRAMP mouse model ( Marhold et al, 2022 ). In addition, increasing evidence suggested that androgen signaling through the androgen receptor ( AR ) contributes to the promotion of castration-resistant prostate cancer ( CR PC) ( Zhou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the basal cell gene-expression profile was found to be significantly enriched in castration-resistant and advanced prostate cancers ( Zhang et al, 2016 ), which indicated basal cells might play a potential role in the development of resistance to anti-androgens in PCa. In a study published by Marhold et al showed that basal cells were involved in primary resistance to androgen receptor inhibition in the TRAMP mouse model ( Marhold et al, 2022 ). In addition, increasing evidence suggested that androgen signaling through the androgen receptor ( AR ) contributes to the promotion of castration-resistant prostate cancer ( CR PC) ( Zhou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, MALAT1 can regulate expression of the androgen receptor and thereby controls proliferation, invasion, and migration of prostate cancer cells. In addition, MALAT1 is believed to downregulate specific types of splicing in patients with metastatic Castrate-resistant prostate cancer ( 128 130 ). MALAT1 is overexpressed and used as a prognostic biomarker in various cancer types including lung, breast, liver, pancreas, renal, colon, bladder, uterus, and cervix cancers ( 131 , 132 ).…”
Section: Functions Of Fusion Genes Involving Ncrnas In Cancermentioning
confidence: 99%
“…MALAT1-MVP and MALAT1-NCBP3: In a prostate cancer mouse model, MALAT1 fusions, including MALAT1-MVP and MALAT1-NCBP3, were found to be implicated in resistance to second-generation antiandrogen cancer drugs ( 130 ). Notably, the fusion partner NCBP3 (Nuclear Cap-Binding Protein 3) is associated with nuclear–cytoplasmic transport ( 136 ), and MVP (major vault protein) is related to multidrug resistance in various malignancies ( 137 ).…”
Section: Functions Of Fusion Genes Involving Ncrnas In Cancermentioning
confidence: 99%